Effects of inter-annual freshwater inflow shifts on the community structure of estuarine decapods - Encarnação, João (2014)
The objective of this study was to evaluate how inter-annual changes in freshwater inputs have affected the decapod assemblages in the Guadiana estuary. Three major areas in the estuary were sampled during the summer, in 2001 (high inflow year and before the filling of the Alqueva dam), in 2002 (low inflow and after filling of the Alqueva dam), and in 2008 and 2009 (low inflow and after consolidation of the impacts of the Alqueva dam). A significant increase in total decapod densities was recorded for the entire estuary, but especially in the upper estuary, after the closure of the dam in 2002. Changes in salinity, turbidity and temperature, which were mainly due to changes in freshwater input and climatic influence (North Atlantic Oscillation index), had an important influence on the structure of the decapod crustacean assemblages. The major conclusions of the study were that, following the construction of the Alqueva dam and regularization of the freshwater inflow, the decapod crustacean community in the Guadiana estuary changed and a shift of the dominant decapod species to upper zones of the estuary happened. These changes, and the presence of the non-native Palaemon macrodactylus in 2008 and 2009, further enhance the importance of estuarine monitoring studies to improve ecologists’ knowledge on distinguishing and understanding natural changes and anthropogenic impacts in the ecosystem.